(untitled) (World Economics and Finance Bulletin, 2023)
Finance professionals are dependent on accounting information provided in annual reports. Companies located in over 144 countries base the preparation of their annual reports on International Financial Reporting Standards (IFRS). This widespread adoption of IFRS has been supported by the assertion that it is an important means of enhancing comparability of financial statements across countries. IFRS are developed in English and translated into 48 languages. Importantly, it is mainly assumed that all translated IFRS convey the same consistent information and that comparability of financial information is not compromised when different languages are used. However, we show in this short communication that differences exist between the IFRS language versions. Our discussion on relevant linguistic effects on the interpretation and application of IFRS helps future research to systematically analyze why equally qualified professionals exercise their professional judgments differently